Enhanced Process Integration of Entrained Flow Gasification and Combined Cycle: Modeling and Simulation Using Aspen Plus. (May 2017) - Darmawan, Arif; Hardi, Flabianus; Yoshikawa, Kunio; Aziz, Muhammad; Tokimatsu, Koji
Abstract: Energy recovery from black liquor can be performed through gasification process at temperatures above the melting point of the inorganic chemicals. Complementing the experimental research, this study was conducted in Aspen Plus software to simulate thermodinamic modeling of detail process for gasification and combined cycle in an integrated system power plant. Mass and energy balances were examined to quantify process performance. The unrecoverable energy in a single process will be utilized in other processes. The combination of these technologies is expected minimizing the total exergy destruction the throughout system. Kraft black liquor was used as sample during process calculation. The proposed integrated-system shows a high energy efficiency. A significant positive energy harvesting from black liquor can be achieved for further development.